Avaliação de métodos de previsão de cargas elétricas em curto prazo para aplicação em sistemas de distribuição inteligentes - Garcia, Lidia Maria Dutra (2013)
In Electric Power Systems understand the future behavior of electric loads is crucial to make a decision. The long, medium and short term load forecast is essential power systems. Considering the gradual transformation of the traditional distribution systems to smart grids, where the electric system automation and online communication are effective, the forecast in very short term gets new challenges. Based on these facts, the objective of this thesis is to identify the most appropriate methods to accomplish these forecasts to contribute to decision-making in distribution systems operation. Various techniques of forecasting and simulations in different methods were studied, in order to identify which of these offers the best results regarding demand the forecast in the very short term. The quantities considered to make predictions and, which have more relevance to the horizon under study are electrical and climate. The methods used in the simulations were the Artificial Neural Networks (ANN) type recurrent Elman e NARX and Neurofuzzy.